Global research dynamics in the Mediterranean diet and diabetes mellitus: a bibliometric study from 2014 to 2024 - Yan, Yuanyuan; Li, Zonghuai; Lian, Yuanchu; Liu, Pingping; Zhang, Bo; Chen, Juan (Frontiers in Nutrition, 2024)
Objective: The Mediterranean diet (MedDiet) has been found to have benefits for diabetes mellitus (DM), but a bibliometric analysis of its association with DM has yet to be conducted. This paper aims to explore the current status and research hotspots on the connection between the Mediterranean diet and DM from 2014 to 2024, providing a reference for future studies.We retrieved articles published between 2014 and 2024 from the Web of Science database and analyzed them using R software, VOSviewer, and CiteSpace.Results: A total of 2,806 articles were included in this study. Research on the relationship between the MedDiet and DM showed a steady increase in publication volume from 2014 to 2019, followed by a sharp rise from 2020 to 2023. Spain was the leading country in terms of publication volume, followed by Italy, the United States, China, and Greece. Spain also led in international collaborations, with CIBER -Centro de Investigación Biomédica en Red and Harvard University being the most prominent collaboration centers. Nutrients was the most frequently published and cited journal in this field. Common keywords in this literature included components such as olive oil, legumes, and red wine. Mechanisms studied in this field primarily focused on antioxidant effects, improvements in insulin sensitivity and secretion, regulation of lipid metabolism, and modulation of gut microbiota.Research on the beneficial effects of the MedDiet on DM patients has garnered significant attention from researchers worldwide, and it is expected to become a major focus for future DM prevention and treatment. This study provides a comprehensive analysis of the current status and research hotspots regarding the relationship between the MedDiet and DM, offering valuable references for future research.